Implementasi Sistem Bagi Hasil dan Perlakuan Akuntansi pada Pembiayaan Mudharabah Di KSPPS BMT An-Nuur Jombang - Miftakhul Rohman Rohman; Rachma Agustina (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2021)
Revenue sharing system is a system that includes the procedure of distribution of business results between the fund owner (shohibul maal) and fund managers (mudharib). The main firmness of this investigating is to knowing the implementation of the share instrumentality in KSPPS BMT An-Nuur Jombang and Assess the conformity of Mudharabah financing accounting treatment with the nutrient of PSAK 105 Mudharabah Accounting. This type of investigating is a quality with a descriptive motion, time the object of this investigating is KSPPS BMT An-Nuur Jombang. The data grouping techniques in this study are observations and interviews and methods of analysis using data reduction.From the results of this study shoed that the procedure system for Mudharabah financing in KSPPS BMT An-Nuur Jombang Implement Revenue Sharing method. In PSAK 105 It is mall that this method makes gross profit as the basis for distributing business results, Accounting attention on Mudharabah financing in KSPPS BMT An-Nuur has not been phase amenable with PSAK 105. Acknowledgement of profit, acknowledgement of loss, acknowledgement of receivables and claim of loss in accordance with PSAK 105.